The Generalized Unit Value Index - Ludwig von Auer (Universität Trier, Fachbereich IV – Volkswirtschaftslehre, 2011)
The inflation rate is normally computed as a weighted average of individual price changes. Alternatively, this rate could be evaluated by comparing average price levels. Unfortunately, this methodology has received limited attention in past research. This study attempts to remedy this situation by introducing a group of Generalized Unit Value indices that evaluate price level changes. The group includes some well-known (Laspeyres, Paasche, Banerjee), hardly known (Lehr, Davies), and previously unknown price indices. An assessment of their axiomatic properties is presented.
Keywords: C43; E31; E52; 330; Index Theory; Inflation; Unit Value; Measurement